Ion irradiation induced surface composition modulation in equiatomic binary alloys - Kim, Byung-Hyun; Kim, Sang-Pil; Kang, Joonhee; Chung, Yong-Chae; Kim, Kyung-Suk; Lee, Kwang-Ryeol (ELSEVIER, 2021)
Composition modulation by Ar bombardment on the Co0.5Cu0.5 alloy and the CoAl B2 phase was investigated on atomic scale by molecular dynamics simulation. The Ar bombardment on alloys at 300 K revealed that this bombardment induces a surface composition modulation in the layer-by-layer mode. In both the Co0.5Cu0.5 alloy and the CoAl B2 phase, the element of higher-sputtering yield is accumulated on the top surface layer, whereas it is depleted in lower layers, which is puzzling in the framework the conventional sputtering theory. A phenomenological kinetic model derived from the MD simulation results considering both the rearrangement and the sputtering of the substrate atoms successfully demonstrated that the rearrangement of the substrate atoms plays a significant role in the observed composition modulation.